Is there an ethical obligation to split every donor liver?: scarce resources, medical factors, and ethical reasoning - Bobbert, Monika; Primc, Nadia; Schäfer, Rebecca Nathalie (Pediatric transplantation, 2019)
SLT has the potential to counter the worldwide shortage of donor organs. Although the preferred recipients of SLT are usually pediatric patients, a more stringent ethical argument than the fundamental prioritization of children is to demonstrate that SLT of deceased donor organs could increase access to this potentially lifesaving resource for all patients, including children. Several empirical studies show that SLT also makes it possible to achieve similar outcomes to WLT in adults if several factors are observed. In general, it can be regarded as ethically permissible to insist on splitting a donor liver if, in an individual case, SLT is expected to have a similar outcome to that of WLT. The question is therefore no longer whether, but under what conditions SLT is able to achieve similar results to WLT. One of the main challenges of the current debate is the restricted comparability of the available data. We therefore have an ethical obligation to improve the available empirical data by implementing prospective clinical studies, SLT programs, and national registries. The introduction of 2 modes of allocation - one for patients willing to accept both SLT and WLT, and a second for patients only willing to accept WLT- would help to resolve the issue of patient autonomy in the case of mandatory splitting policy.
Gesehen am 02.06.2020